(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Near 40% of the aggregate number of Poland’s inhabitants live in rural areas. For thestructure of age, profitable transformations of other structures and coefficients ofreproduction introduced in this elaboration – demographic resources of rural areasdetermine the significant development potential. We ought to do our best, to make thefull use of it. Versatile rural development should be the main direction of the activation